Characterization of Piezoelectric Properties of Ag-NPs Doped PVDF Nanocomposite Fibres Membrane Prepared by Near Field Electrospinning - Pan, Cheng-Tang; Dutt, Karishma; Yen, Chung-Kun; Kumar, Ajay; Kaushik, Aman C.; Wei, Dong-Qing; Kumar, Amit; Wen, Zhi-Hong; Hsu, Wen-Hsin; Shiue, You-Ling (Combinatorial Chemistry & High Throughput Screening, 2022)
Background: In this study, Near-field electrospinning (NFES) technique is used with a cylindrical collector to fabricate a large area permanent piezoelectric micro and nanofibers by a prepared solution. NFES requires a small electric field to fabricate fibers Objective: The objective of this paper to investigate silver nanoparticle (Ag-NP)/ Polyvinylidene fluoride (PVDF) composite as the best piezoelectric material with improved properties to produced tremendously flexible and sensitive piezoelectric material with pertinent conductance Methods: In this paper, we used controllable electrospinning technique based on Near-field electrospinning (NFES). The process parameter for Ag-NP/PVDF composite electrospun fiber based on pure PVDF fiber. A PVDF solution concentration of 18 wt.% and 6 wt.% silver nitrate, which is relative to the weight of PVDF wt.% with 1058 μS conductivity fibers, have been directly written on a rotating cylindrical collector for aligned fiber PVDF/Ag-NP fibers are patterned on fabricated copper (Cu) interdigitated electrodes were implemented on a thin flexible polyethylene terephthalate (PET) substrate and Polydimethylsiloxane (PDMS) used as a package to enhance the durability of the PVDF/ Ag-NP device. Results: A notable effect on the piezoelectric response has been observed after Ag-NP addition, confirmed by XRD characterization and tapping test of Ag-NP/PVDF composite fiber. The morphology of the PVDF/Ag-NP fibers and measure diameter by scanning electron microscopy (SEM) and Optical micrograph (OM), of fiber. Finally, a diameter of PVDF/Ag-NP fibers up to ∼7 μm. The high diffraction peak at 2θ = 20.5˚ was investigated by X-ray diffraction (XRD) in the piezoelectric crystal β-phase structure. Further addition of silver nanoparticles (Ag- NPs) in the PVDF solution resulted in enhancing the electromechanical conversion of the fibers from ∼0.1 V to ∼1 V. Conclusion: In conclusion, we can say that confirmed and validated the addition of Ag-NP in PVDF could enhance the piezoelectric property by using NFES technique with improved crystalline phase content can be useful for a wide range of power and sensing applications like biomedical devices and energy harvesting, among others.
Keywords: polymer solution